Caccia e territorio Evoluzione della disciplina normativa in Toscana - Corinto, Gian Luigi (Strumenti per la didattica e la ricerca, 2017)
Despite a feeling of clear opposition towards hunting is widely spread, it does not seem possible to imagine a world in which the hunting practice is completely eliminated. Hunting, or rather and more generally wildlife hunting activities, have deep historical and cultural roots. In recent times, ethical and cultural sensibilities and views, as well as personal and collective choices (all very legit) have emerged around the hunting activity. This study therefore offers a broad overview of the changes which have taken place in hunting wildlife policies, with particular reference to Tuscany.